PANDANGAN HUKUM ISLAM TENTANG PROBLEMATIKA PEMBAGIAN HARTA WARISAN DALAM MASYARAKAT ADTA JAWA DI DESA SENGGRONG KECAMATAN ANDONG KABUPATEN BOYOLALI TAHUN 2022 - Muhammad, Ade; Isfihani, I; Fatuh, Agus (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
The view of islamic law regarding the distribution of inheritance in the andong boyolali community, which uses javanese customary law in the method of inheritance distribution, causes many problems in the distribution of inheritance and conflicts over the rights of the assets obtained. This article is intended to provide understanding and explain especially to the dignitaries in the community and in general to the general public regarding the distribution of inheritance in accordance with islamic law based on the koran, hadith and ijma of the ulama, so as not to cause many problems in the distribution of inheritance. And acquired property rights. The type of research that will be used in this study is qualitative research with qualitative descriptive data collection techniques in the form of observation, interviews, and documentation. Intended to obtain information and existing data, which relates to the problem of the many problems in the distribution of inheritance. In this study, the authors focus on the analysis of the views of islamic law.